Pengaruh Perkembangan Islam terhadap Dunia Pendidikan di Indonesia: Sebuah Kajian Historis - Purnamasari, Ika; Safitri, Fivie; Asrul, Annisa Aprilia; Muham, Setia Esra S.; Perangin-angin, Desta Riani Br. (Medan Resource Center, 2024)
This research aims to examine the influence of Islamic developments on the world of education in Indonesia from a historical perspective. Since the arrival of Islam to the archipelago in the 13th century, this religion has made a significant contribution to the formation of the education system in this region. Through madrasas, Islamic boarding schools and Islamic schools, Islamic teachings have been absorbed into the educational curriculum which includes religious, moral and general knowledge lessons. This research uses historical methods with a qualitative approach to analyze data from various primary and secondary sources, including manuscripts, historical documents and academic literature. The results of the study show that Islamic education not only plays a role in spreading religion, but also in forming the character, ethics and intellect of Indonesian society. Apart from that, the development of Islamic education also adapts to social and political dynamics, and contributes to the progress of national education in the modern era. These findings confirm that Islamic education has a strategic role in the formation of identity and the development of educational culture in Indonesia.